Ayat-ayat Terkait Radikalisme dalam Al-Qur’an - Muhammad Miftah Fauzi; Muhammad Taufik Faturrahman; Muhammad Fawwaz Dwizahran; Rasihon Anwar; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
There is often a history of radicalism and terrorism in the name of religion. It is clear from these actions that religious dogma has considerable power. Including Islam, which from the beginning claimed to have principles of peace, these principles were used by a handful of people as a claim to commit violence. One of the causes is a misunderstanding of the Qur'anic verses and Prophetic Hadiths about jihad and Qital. This paper aims to examine the verses related to radicalism and terrorism by using the at-tafsir al-mawdu'iy method, which is by collecting all Qur'anic verses that have the same purpose and theme. The results of the study show that Islam is in principle strongly opposed to radicalism and terrorism and concludes that jihad and war (qital) in the Qur'an are different from acts of radicalism and terrorism. The main purpose of jihad is to refer to human welfare rather than conflict. Thus, jihad is unconditional and unrestricted, making it the responsibility of Muslims at all times. As for qital, it is limited by certain circumstances and is only used as a last resort when all other options have failed.